Effect of Fenton-Based Processes on Arsenic Removal in the Presence of Humic Acid - Wenming Xiong; Qixuan Huang; Langlang Li; Yongjun Li (Toxics)
Geogenic arsenic (As) contamination in groundwater poses a significant public health risk in many regions worldwide. Previous studies have reported hydrogen peroxide (H2O2) concentrations ranging from 5.8 to 96 μmol L−1 in rainwater, which may contribute to the oxidation and removal of As. However, the influence of natural organic matter, such as humic acid (HA), on rainwater-borne H2O2-induced Fenton processes for the oxidation and removal of As remains unclear. In this study, the Fenton process was employed to investigate changes in As(V), As(III), and their mixtures, both in the presence and absence of HA. The results showed that low concentrations of HA (0–10 mg/L) promoted the oxidation of As(III) and removal of As(V) when As(V) and As(III) were present individually. However, when As(V) and As(III) coexisted, HA inhibited the Fenton process for As(V) removal. This inhibition was likely due to As(III) competing strongly with HA for hydroxyl radicals in the Fenton reaction system. Additionally, the presence of HA hindered the Fe(III)-driven removal of As(V), a product of the Fenton reaction. These findings further enhance our understanding of the potential role of rainwater-borne H2O2 in the transformation of As species in open water environments.